ANALYSIS OF THE ROLE OF LAW IN REGULATING ELECTRONIC TRANSACTIONS IN E-COMMERCE - DARRYL ANNE LANITA SIMANUNGKALIT; SITI NUR AMALIAH; ADINDA ZAHRA ANDRIYANI; ANDRIYANTO ADHI NUGROHO (CV KULTURA DIGITAL MEDIA, 2024)
This research analyzes the role of law in regulating electronic transactions in e-commerce. Along with the rapid development of information technology, e-commerce has become an important pillar in the global economy. However, the complexity and dynamics of electronic transactions pose significant legal challenges. This study aims to identify and surface the existing legal framework, including the Information and Electronic Transactions Law (UU ITE) in Indonesia, as well as international regulations related to e-commerce. This research also examines consumer protection, data security, privacy, and settlement mechanisms relevant to electronic transactions. Through normative juridical analysis and a comparative approach, this research found that even though there is a fairly comprehensive legal framework, there are still weaknesses in the implementation and enforcement of the law that need to be addressed. In conclusion, to create a safe and trustworthy e-commerce environment, more adaptive regulatory improvements and more effective law enforcement are needed.